KEWENANGAN PENGELOLAAN DESA WISATA DALAM PERSPEKTIF PERATURAN DAERAH PROVINSI BALI NOMOR 4 TAHUN 2019 TENTANG DESA ADAT DI BALI - A.A. Istri Eka Krisna Yanti (Kerta Dyatmika, 2019)
This study is entitled "The Authority of Tourism Village Management in the Perspective of Bali Provincial Regulation Number 4 of 2019 Regarding Desa Adat." The initial idea of this study originated from the norms in the formation of a tourist village so that the principles and objectives of tourism have not yet been achieved, especially the welfare of the local community, namely â€œKrama Desa Adatâ€, as implementers, implementers, conservationists and agricultural developers in Bali. Balinese culture as the main foundation of tourism development that is able to prosper the local community. This research focuses on two legal issues namely, How is the authority of the Provincial Government of Bali in preparing Local Regulations on Tourism Villages? How is the authority of Desa Adat in the management of Tourism Villages based on Regional Regulation Number 4 of 2019 About Desa Adat.?The research method that used in this thesis is normative legal research methods. Normative legal research is done by analyzed relevant legislation and literature. The approach used is statue approach and conceptual approach Both of these problems were examined using normative legal research methods and using relevant legal theories to analyze these problem.Based on the analysis, it is known that the Provincial Government has the authority to cerate Regional Regulations to guarantee legal certainty in organizing a Tourism Village in the Province so that it is in accordance with the principles and objectives of tourism, namely the welfare of the community, especially Krama Desa Adat.Keywords: Authority, Tourism Village, Tourism, Customary Village.